Composition of intestinal microbial communities in the large intestine of rats before and after T. gondii infection. - Ji-Xin Zhao (22056386) (2025)
(A–B) Bar plots illustrating taxonomic composition at the phylum and species levels across different groups before and after infection. (C) Box plots depicting the relative abundance of major bacterial phyla, including Verrucomicrobiota, Actinomycetota, Pseudomonadota, Thermodesulfobacteriota and Spirochaetota, at different infection stages. (D) Box plots illustrating changes in the relative abundance of representative bacterial species, including Lactobacillus johnsonii, Liqilactobacillus murinus, Akkermansia muciniphila and Limosilactobacillus reuteri, following T. gondii infection. Statistical significance was assessed using the Wilcoxon rank-sum test: * P < 0.05; **P < 0.01.